2011
DOI: 10.1371/journal.pbio.1001192
|View full text |Cite
|
Sign up to set email alerts
|

Sperm-Storage Defects and Live Birth in Drosophila Females Lacking Spermathecal Secretory Cells

Abstract: Transgenic Drosophila are used to identify the functions of a small set of secretory cells that are typically associated with the sperm-storage organs of female insects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
122
0
3

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(138 citation statements)
references
References 56 publications
13
122
0
3
Order By: Relevance
“…For example, in the beetle, Drusilla canaliculata, sperm migrate into the spermathecae (41), whereas the spermathecal gland in the boll weevil, Anthonomus grandis, is required for sperm activation, storage, clearance, and fertility (42,43) In D. melanogaster, sperm swim backward upon entering the female reproductive tract, and genetic ablation of the spermatheca secretory cells (SSCs) before mating leads to sperm storage defects: sperm fail to migrate into spermathcae and become inactive within the seminal receptacle (44)(45)(46). Moreover, SSC-ablated females display reduced fertility over time and ovovivipary (47). These experiments suggest that substances in spermathecae, SSCs, or perhaps other tissues are involved in the activation and chemoattraction of insect sperm (48).…”
Section: Significancementioning
confidence: 99%
“…For example, in the beetle, Drusilla canaliculata, sperm migrate into the spermathecae (41), whereas the spermathecal gland in the boll weevil, Anthonomus grandis, is required for sperm activation, storage, clearance, and fertility (42,43) In D. melanogaster, sperm swim backward upon entering the female reproductive tract, and genetic ablation of the spermatheca secretory cells (SSCs) before mating leads to sperm storage defects: sperm fail to migrate into spermathcae and become inactive within the seminal receptacle (44)(45)(46). Moreover, SSC-ablated females display reduced fertility over time and ovovivipary (47). These experiments suggest that substances in spermathecae, SSCs, or perhaps other tissues are involved in the activation and chemoattraction of insect sperm (48).…”
Section: Significancementioning
confidence: 99%
“…Both Nep1 and Nep2 are highly expressed in the CNS and the spermathecae, two tissues that are known to influence egg laying (Yang et al 2009;Schnakenberg et al 2011;Sun and Spradling 2013). Nep2 is also expressed in the border cells of the follicular epithelium, which are important for micropyle development and for anterior-posterior polarity in the egg (Furriols et al 2007).…”
Section: Characterization Of the Hatchability Defects In Nep2 Null Mumentioning
confidence: 99%
“…Studies in Drosophila have shown that the sperm storage organs act to nourish and protect sperm by creating an appropriate environment through secretion: genetic or targeted disruption of the secretory glandular cells or of the secretory pathway results in nonfunctional spermathecae and reduced fertility phenotypes (8)(9)(10)(11). Transcriptional and proteomic profiling of sperm storage organs and their secretions in Drosophila and Apis have identified pathways involved in carbohydrate and lipid metabolism, oxidative stress, and antimicrobial responses that are likely to play roles in nourishing and/or protecting sperm from damage caused by infection and reactive oxygen species (ROS) (9,(12)(13)(14)(15).…”
mentioning
confidence: 99%